Step 1

Given:

x+2y=8...(i)

Put x=-5 in (i)

\(\Rightarrow -5+2y=8\)

\(\Rightarrow 2y=8+5\)

\(\Rightarrow y=\frac{13}{2}\)

So \(x=-5, y=\frac{13}{2}\)

Put \(x=-5, y=\frac{13}{2}\) in (i)

\(\Rightarrow -5+2(\frac{13}{2})=-5+13=8=8\)

So the equation are true.

Given:

x+2y=8...(i)

Put x=-5 in (i)

\(\Rightarrow -5+2y=8\)

\(\Rightarrow 2y=8+5\)

\(\Rightarrow y=\frac{13}{2}\)

So \(x=-5, y=\frac{13}{2}\)

Put \(x=-5, y=\frac{13}{2}\) in (i)

\(\Rightarrow -5+2(\frac{13}{2})=-5+13=8=8\)

So the equation are true.